Yoga: Alternative science for caring pregnancy women - Somsap , Yaowares (Nursing Journal CMU, 2021)
The caring pregnancy women by the midwife target on the holistic health of body, mind, emotion, social and spiritual and also make the baby healthy. By using Yoga techniques apply for the caring pregnancy women, under the Yoga formula teach the positive attitude, exercise the body with Asana, control the respiration and their mind. That can help pregnancy women facing the development during pregnancy confidently, maintain wellness and quality of life. This article has the objective in introducing the background of Yoga and also the concept the principle “Yoga sutra”, the guidelines of caring pregnancy women, the useful for their health and babies, By using the role of the midwife apply the Yoga with the pregnancy women and concern the factors for using. The midwife should support the pregnancy women practicing yoga because of this is the natural ways, high potency and help them in the holistic health.